PENGARUH KOMITMEN ORGANISASIONAL, PENGEMBANGAN KARYAWAN DAN BUDAYA ORGANISASI TERHADAP KOMPETENSI KARYAWAN PT. WASKITA KARYA (PERSERO) TBK CABANG PEKANBARU - Fajri Mubarak Natsir; Taufiqurrahman '; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Waskita Karya (Persero) Tbk Pekanbaru Branch in order to determine the effect of Organizational Commitment, Employee Development and Culture Organization simultaneously on Employees Competence PT. Waskita Karya (Persero) Tbk Pekanbaru Branch. This study uses primary data obtained from interviews and giving questionnaires to all employess of PT. Waskita Karya (Persero) Tbk Pekanbaru Branch. Secondary data were obtained relating to the object and the organizational structure of the population in this study were all employess of 40 persons and sampled. The analytical method used in this research is multiple linier regression method. From the testing that has been done, simultannous regression test (Test-F) showed that the variables of Organizational Employee Development and Culture Organization simultaneously significant effect on employee competency. From the results of the parial test (t-test) showed that the variables of Organizational Employee Development and Culture Organization have significant effect on employess competency. The result of the calculation of the coefficient of determination (R2) is equal to 0.720, which means, variable Organizational Commitment, Employee Development and Culture Organization jointly affect the Employee Competency, while the rest influenced by other variables not examinet in this study.Keyword: Organizational Commitment, Employee Development, Organizational Culture and Employee Competency Commitment